1993
DOI: 10.12935/jvma1951.46.952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pirenoxine Ophthalmic Solution on Senile Incipient Cataract in Dogs

Abstract: Pirenoxine ophthalmic solution, an anticataract drug for human use , was tested for its effectiveness in the treatment of senile incipient cataract in dogs . Of 18 cases treated with the drug, 13 (72.2%) cases responded favorably resulting in improved lens opacity or delayed progress of the disease . Hyperemia and epiphora, both being local sensitive symptoms, were obsereved in one case . Improved lens opacity was noticeable after medication for 81.6 days on average, and the effect was pronounced in younger ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Eye drops containing antioxidants, as well as oral antioxidants, have been widely used in humans and dogs. Pirenoxine antioxidant eye drops were reported to suppress the progression of presbyopia in rats and also reduce lens opacity and delayed cataract progression in dogs [ 26 27 28 ]. Additionally, the instillation of eye drops containing N-acetyl carnosine, another antioxidant, resulted in the delayed progression of senile cataracts and subtle reduction in the opacification of the lens in humans and dogs [ 3 21 29 30 31 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eye drops containing antioxidants, as well as oral antioxidants, have been widely used in humans and dogs. Pirenoxine antioxidant eye drops were reported to suppress the progression of presbyopia in rats and also reduce lens opacity and delayed cataract progression in dogs [ 26 27 28 ]. Additionally, the instillation of eye drops containing N-acetyl carnosine, another antioxidant, resulted in the delayed progression of senile cataracts and subtle reduction in the opacification of the lens in humans and dogs [ 3 21 29 30 31 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies revealed that PRX decelerated lens opacity and slowed the progression of age-related cataract [ 27 , 28 ]. Of these findings, one study showed that the effects of PRX were noticeable after 81.6 days of treatment [ 27 ].…”
Section: Effects Of Pirenoxine On Age-related Cataract: Evidence From...mentioning
confidence: 99%
“…In vivo studies revealed that PRX decelerated lens opacity and slowed the progression of age-related cataract [ 27 , 28 ]. Of these findings, one study showed that the effects of PRX were noticeable after 81.6 days of treatment [ 27 ]. Interestingly, these beneficial effects were more prominent in the cortical region of the lens, especially in younger models [ 27 ].…”
Section: Effects Of Pirenoxine On Age-related Cataract: Evidence From...mentioning
confidence: 99%
See 2 more Smart Citations